Toxoplasma gondii infection in pig intended for human consumption: seroprevalence, risk factors and influence of biosecurity measures - Scofano, Agostinho Sergio; Arruda, Igor Falco; Teixeira, Jessica Nogueira [UNESP]; da Cunha, Nathalie Costa; Do Nascimento, Elmiro Rosendo; Amendoeira, Maria Regina Reis; Millar, Patrícia Riddell (FapUNIFESP (SciELO), 2023)
A serologic and epidemiologic study was carried out in order to determinate herd and animal seroprevalence and associated factors for Toxoplasma gondii in commercial pigs from Espírito Santo state, Brazil. Blood samples were collected from 416 pigs from 55 producer farms in 27 municipalities. An indirect immunofluorescent assay (IFA) was performed to estimate the seroprevalence of T. gondii and identify the associated risk factors using a questionnaire. The T. gondii antibody prevalence rate in commercial swine herds was 15.4% (64/416) using a cutoff of 1:64. The seropositivity for T. gondii was related to the presence of cats, water origin and age of swine in the increase of seroprevalence, and the existence of internal isolation fences and use of composting chambers as protective factors. To the best of our knowledge, this is the first study to report anti-T. gondii antibodies in the serum of pigs in the state of Espírito Santo, Brazil. This finding is important to public health because seropositive pigs can harbor tissue cysts in their meat, thereby representing a zoonotic risk for consumers of raw or undercooked porcine meat or its products.
Infecção por Toxoplasma gondii em suínos destinados ao consumo humano: soroprevalência, fatores de risco e influência de medidas de biosseguridade
Keywords: infectious diseases; public health; swine; Toxoplasmosis; zoonosis